2011
DOI: 10.3168/jds.2010-3319
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of bovine β-lactoglobulin against mastitis-causing bacteria

Abstract: Bovine mastitis is one of the most economically deleterious diseases affecting dairy herds and results from an infection of the udder by pathogenic microorganisms such as Staphylococcus aureus, Streptococcus uberis, and Escherichia coli. The mammary gland is capable of preventing and combating bacterial infection by means of a complex network of innate and adaptive immune mechanisms. Lactoferrin is an 86-kDa protein with antibacterial activity that plays a role in the mammary gland's defense against infection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Mild growth inhibitory activity of pure β-LG against growth of Gram positive S. aureus strains was already reported in literature (Chaneton, Pérez Sáez, J. M., & Bussmann, 2011), which confirms the present results. On the other hand no effect of pure β-LG against resting cells of Pseudomonas fluorescens, Pseudomonas fragi and Bacillus subtilis was observed (Pan et al, 2007).…”
Section: Antibacterial Activitysupporting
confidence: 93%
“…Mild growth inhibitory activity of pure β-LG against growth of Gram positive S. aureus strains was already reported in literature (Chaneton, Pérez Sáez, J. M., & Bussmann, 2011), which confirms the present results. On the other hand no effect of pure β-LG against resting cells of Pseudomonas fluorescens, Pseudomonas fragi and Bacillus subtilis was observed (Pan et al, 2007).…”
Section: Antibacterial Activitysupporting
confidence: 93%
“…Up to 4% native WPI was previously described to have a mild antimicrobial activity against E. coli ATCC 8739 and S. aureus Mu50, although there was no complete growth inhibition observed . Similarly, pure β-LG was found to have a mild effect against S. aureus strains (Chaneton, Perez Saez, & Bussmann, 2011). Some protein modifications that introduced strongly charged groups to β-LG, such as amidation, were found to result in bactericidal effects, and it was proposed that the antibacterial effect was somehow connected to the surface charge as well as the charge distribution (Pan et al, 2007).…”
Section: Antibacterial Activity Of Proteinsmentioning
confidence: 99%
“…Numerous studies indicate that LG possesses extra functions which include antimicrobial and antioxidant activities [20, 21]. Chaneton et al identified LG's antimicrobial activity while studying bacterial infection of the mammary glands [22]. …”
Section: Introductionmentioning
confidence: 99%